2016
DOI: 10.1093/femsle/fnw018
|View full text |Cite
|
Sign up to set email alerts
|

APseudomonas putidadouble mutant deficient in butanol assimilation: a promising step for engineering a biological biofuel production platform

Abstract: Biological production in heterologous hosts is of interest for the production of the C4 alcohol (butanol) and other chemicals. However, some hurdles need to be overcome in order to achieve an economically viable process; these include avoiding the consumption of butanol and maintaining tolerance to this solvent during production. Pseudomonas putida is a potential host for solvent production; in order to further adapt P. putida to this role, we generated mini-Tn5 mutant libraries in strain BIRD-1 that do not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…The aceA gene encoding an isocitrate lyase in glyoxylate bypass was proven to be important for acetate, ethanol, poly‐3‐hydroxybutyrate, alkane metabolisms (Sabirova et al ., , ; Jung et al ., ; Zhang and Bryant, ; Ahn et al ., ; Dunn et al ., ). Interestingly, butanol metabolism appeared to occur through the glyoxylate bypass in Pseudomonas putida BIRD‐1 (Cuenca Mdel et al ., ,b) and loss of ethanol and acetate metabolisms was also observed in Candida albicans lacking the isocitrate lyase (Lorenz and Fink, ). Alkane degradation generates the TCA cycle intermediates from acetyl‐CoA via the glyoxylate bypass.…”
Section: Discussionmentioning
confidence: 91%
“…The aceA gene encoding an isocitrate lyase in glyoxylate bypass was proven to be important for acetate, ethanol, poly‐3‐hydroxybutyrate, alkane metabolisms (Sabirova et al ., , ; Jung et al ., ; Zhang and Bryant, ; Ahn et al ., ; Dunn et al ., ). Interestingly, butanol metabolism appeared to occur through the glyoxylate bypass in Pseudomonas putida BIRD‐1 (Cuenca Mdel et al ., ,b) and loss of ethanol and acetate metabolisms was also observed in Candida albicans lacking the isocitrate lyase (Lorenz and Fink, ). Alkane degradation generates the TCA cycle intermediates from acetyl‐CoA via the glyoxylate bypass.…”
Section: Discussionmentioning
confidence: 91%
“…However, the process was restricted by solvent‐sensitivity and the limited activity of the Lactococcus lactis keto‐acid decarboxylase used. The same pathway was explored in solvent‐tolerant aerobic Pseudomonas strains; however, the strain metabolizes butanol, and different metabolic blocks were needed to achieve significant butanol productivity (Cuenca et al ., ).…”
Section: First‐generation (1g) Biofuels and Bioproductsmentioning
confidence: 97%
“…However, the process was restricted by solvent-sensitivity and the limited activity of the Lactococcus lactis keto-acid decarboxylase used. The same pathway was explored in solvent-tolerant aerobic Pseudomonas strains; however, the strain metabolizes butanol, and different metabolic blocks were needed to achieve significant butanol productivity (Cuenca et al, 2016). Atsumi et al (2008) reported titres of 22 g l À1 of isobutanol with engineered Escherichia coli strains that produced this alcohol using diversion of central metabolites in the valine biosynthetic pathway, and Baez et al (2011) reported that the engineered E. coli (JCL260) strain produced more than 50 g l À1 in 72 h if isobutanol was removed from the bioreactor using gas stripping.…”
Section: First-generation (1g) Biofuels and Bioproductsmentioning
confidence: 99%
“…In addition to the lytic cycle, temperate phages also have a lysogenic cycle, in which phages incorporate their genomes into a host chromosome (or maintain their genome extrachromosomally) and replicate with it without lysing their host cells (Howard-Varona et al, 2017). Therefore, temperate phages are considered as natural vectors for gene transmission among bacteria and play important roles in virulence of bacterial pathogens (Boyd, 2012;Cuenca Mdel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many effector proteins, which are bacterial virulent factors and are injected into host cells by bacterial type III secretion system to help bacterial invasion and survival, were identified in Salmonella typhimurium phages (Figueroa-Bossi et al, 2001). Infection with such temperate phages might lead to the transmission of the virulent genes, thus increases the virulence of host bacteria (Cuenca Mdel et al, 2016). Additionally, it was reported that temperate staphylococcal phage 80α could efficiently encapsidate and transfer bacterial pathogenicity island, SaPI1, to a recipient strain (Ruzin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%